BLUE ECONOMY DAN EKONOMI SYARIAH: STUDI PENGELOLAAN SUMBER DAYA PESISIR PADA KOMUNITAS NELAYAN BAJOE KABUPATEN BONE - Mirna Mirna; Muhammad Yamin Muhammad Yamin; Kamiruddin Kamiruddin (STKIP Subang, 2026)
This study aims to examine the application of the blue economy concept in the coastal community of Bajoe and to analyze its relevance to the principles of Islamic economics (ekonomi syariah). This research was driven by the significant untapped marine resource potential in the Bajoe coastal area and the importance of applying Islamic economic values to the community’s economic activities. A qualitative descriptive method with a case study approach was employed. Data were collected through observation, interviews, and documentation involving fishermen, community figures, and relevant stakeholders in Bajoe Village, Tanete Riattang Timur District, Bone Regency. Data analysis utilized the Miles and Huberman model comprising data reduction, data display, and conclusion drawing. The results indicate that implementation of the blue economy concept has begun, evidenced by the use of environmentally friendly traditional fishing tools and growing community awareness of marine conservation. However, implementation remains suboptimal due to persisting environmentally destructive fishing practices, declining marine environmental quality, increasing number of fishermen, and marine product utilization dominated by the sale of raw fish without value-added processing. From the Islamic economics perspective, the blue economy concept is relevant to the principles of maslahah (public welfare), justice, amanah (trustworthiness), and environmental preservation (hifz al-bi’ah). Nevertheless, some community practices still do not fully align with Islamic economic values, particularly regarding marine resource exploitation and unsustainable environmental management.